Direct versus translated writing: the effect of translation on learners’ second language writing ability - Tavakoli, Mansoor; Ghadiri, Momene; Zabihi, Reza (Penerbit UKM, 2014)
A growing body of research has been investigating how L2 writers, while writing in the second language (L2), make use of their first language (L1). In view of this, the present study was conducted to examine the effect of translation on the enhancement or deterioration of Iranian Elementary EFL learners’ writing ability. The participants (N = 60) were prompted to perform two writing tasks: (a) writing directly in English (learners’ L2) and (b) writing in their L1 (Persian) and then translating it into English. They were also assigned a checklist, a retrospective verbal report, to express their attitudes towards the two modes of writing. Analysis of the results revealed that although translation may be of help to some learners, it cannot be an effective strategy to enhance the writing ability of all learners. In effect, the results indicated that there was a significant difference between two writing tasks in terms of using expressions, transitions, and grammatical points. What was of particular interest to the authors was the fact that direct writing did not seem to be as direct as it was expected. The vast majority (75%) of students reported they think in Persian, as “often” or “always” while doing the English task in the direct writing mode. This finding suggests that teachers should incorporate translation strategies into their writing courses and explicitly teach students how to employ effective strategies in different situations. The provision of instruction and practice in using L1, particularly in planning and organizing learners’ writings, may be of benefit to some learners in performing certain writing tasks.